Christ's Body Is One: Resources for Reformed Catholicity in John W. Nevin's Incarnational Ecclesiology - Wood, James Rutland (Journal of reformed theology, 2020)
This essay argues that the ecclesiology of John W. Nevin furnishes American Presbyterians, both evangelical and mainline, with significant resources for the pursuit of Reformed catholicity. Nevin believed that the church must exhibit contemporary unity and historical continuity as a result of its mystical union with the incarnate Christ. He opposed the forces prevalent in American Protestantism that undermined visible, catholic unity. In Nevin's assessment, the foundational factor in these ecclesiological errors was a defective, truncated Christology. Nevin sought to renew Reformed theology through retrieving an orthodox ecclesiology rooted in a robust understanding of the incarnation. The concluding section will argue that both streams of American Presbyterianism fall short in terms of catholicity and would benefit by attending to Nevin's ecclesial vision.